Insights from linking routinely collected data across Australian health jurisdictions: a case study of end-of-life health service use - Julia M Langton; David Goldsbury; Preeyaporn Srasuebkul; Jane M Ingham; Dianne L O’Connell; Sallie-Anne Pearson (Public Health Research & Practice, 2018)
Objectives: The jurisdictional nature of routinely collected health data in Australia has created challenges for linking data across state/territory and federal government boundaries. This has impeded understanding of the interplay between service use across hospital and community care. Our objective was to demonstrate the value-add of cross-jurisdictional data using a case study of health service use and the factors associated with healthcare use towards the end of life.